Chorea-ballism as a manifestation of decompensated type 2 diabetes mellitus - Chang, Claudia Veiga; Felicio, Andre Carvalho; Godeiro, Clecio de Oliveira; Matsubara, Luiz Shiguero; Duarte, Daniela Rezende; Ferraz, Henrique Ballalai; Okoshi, Marina Politi (Lippincott Williams & Wilkins, 2007)
Chorea and ballism are movement disorders that result from a variety of conditions. Hyperglycemia is an unusual recognized cause of these movement disorders. We report 3 cases of new-onset choreaballism induced by nonketotic hyperglycemia in elderly patients, highlighting that chorea may be the first manifestation of undiagnosed decompensated diabetes mellitus.
Keywords: hyperglycemia; diabetes mellitus; chorea; ballism; putamen